Aerosol assisted solvent treatment: a universal method for performance and stability enhancements in perovskite solar cells - Du,T; Ratnasingham,SR; Kosasih,FU; Macdonald,T; Mohan,L; Augurio,A; Ahli,H; Lin,C-T; Xu,S; Xu,W; Binions,R; Ducati,C; et al. (Advanced Energy Materials, 2021)
Metal-halide perovskite solar cells (PSCs) have had a transformative impact on the renewable energy landscape since they were first demonstrated just over a decade ago. Outstanding improvements in performance have been demonstrated through structural, compositional, and morphological control of devices, with commercialization now being a reality. Here the authors present an aerosol assisted solvent treatment as a universal method to obtain performance and stability enhancements in PSCs, demonstrating their methodology as a convenient, scalable, and reproducible post-deposition treatment for PSCs. Their results identify improvements in crystallinity and grain size, accompanied by a narrowing in grain size distribution as the underlying physical changes that drive reductions of electronic and ionic defects. These changes lead to prolonged charge-carrier lifetimes and ultimately increased device efficiencies. The versatility of the process is demonstrated for PSCs with thick (>1 µm) active layers, large-areas (>1 cm2) and a variety of device architectures and active layer compositions. This simple post-deposition process is widely transferable across the field of perovskites, thereby improving the future design principles of these materials to develop large-area, stable, and efficient PSCs.